PENGARUH LIKUIDITAS, PROFITABILITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Sektor Consumer Goods Yang Tercatat Di Bursa Efek Indonesia Periode 2017-2022) - Restu Putra, Dany Mashehi; Rosdiana, Riska (Universitas Mercu Buana, 2024)
This study aims to examine the effect of liquidity, profitability, solvency, and company size on firm value in Consumer Goods sector companies listed on the Indonesia Stock Exchange in 2017-2022. The method used in this study is a quantitative method with a panel data regression analysis approach using software review 10. The data used comes from the financial statements of consumer goods sector companies listed on the Indonesia Stock Exchange during the study period. There are 28 companies that meet the limitations in the consumer goods sector listed on the Indonesia Stock Exchange for 2017-2022. The research results that Current Ratio has no effect on Price to Book Value, Debt to Equity Ratio has a positive and significant effect on Price to Book Value, Return On Assets has a significant positive effect on Price to Book Value, and firm size has no significant and positive effect on Price to Book Value.